Dust Deposited on Snow Cover in the San Juan Mountains, Colorado, 2011–2016: Compositional Variability Bearing on Snow‐Melt Effects. Issue 7 (13th April 2020) - Reynolds, Richard L.; Goldstein, Harland L.; Moskowitz, Bruce M.; Kokaly, Raymond F.; Munson, Seth M.; Solheid, Peat; Breit, George N.; Lawrence, Corey R.; Derry, Jeff
Abstract: Light‐absorbing particles in atmospheric dust deposited on snow cover (dust‐on‐snow, DOS) diminish albedo and accelerate the timing and rate of snow melt. Identification of these particles and their effects is relevant to snow‐radiation modeling and water‐resource management. Laboratory‐measured reflectance of DOS samples from the San Juan Mountains (USA) were compared with DOS mass loading, particle sizes, iron mineralogy, carbonaceous matter type and content, and chemical compositions. Samples were collected each spring for water years 2011–2016, when individual dust layers had merged into one (all layers merged) at the snow surface. Average reflectance values of the six samples were 0.2153 (sd, 0.0331) across the visible wavelength region (0.4–0.7 μm) and 0.3570 (sd, 0.0498) over the full‐measurement range (0.4–2.50 μm). Reflectance values correlated inversely to concentrations of ferric oxide, organic carbon (1.4–10 wt.%), magnetite (0.05–0.13 wt.%), and silt (PM63‐3.9; median grain sizes averaged 21.4 μm) but lacked correspondence to total iron and PM10 contents. Measurements of reflectance and Mössbauer spectra and magnetic properties indicated that microcrystalline hematite and nano‐size goethite were primarily responsible for diminished visible reflectance. Positive correlations between organic carbon and metals attributed to fossil‐fuel combustion, with observations from electron microscopy, indicated that some carbonaceous matter occurred as black carbon. Magnetite was a surrogate for related light‐absorbing minerals, dark rock particles, and contaminants. Similar analyses of DOS from other areas would help evaluate the influences of varied dust sources, wind‐storm patterns, and anthropogenic inputs on snow melt and water resources in and beyond the Colorado River Basin. Plain Language Summary: Melted snow from mountains is a critical source of water for people and agriculture downstream, and the rate and timing of snow melt are important factors for water management. Along with air temperature, certain mineral and carbon‐rich particles deposited as atmospheric dust on snow cover greatly affect snow melt because they absorb sunlight to warm snow. To understand better how snow melts, we identified these kinds of heat‐absorbing particles in end‐of‐melt season, dark dust layers spanning 6 years (2011–2016) in the San Juan Mountains in the upper Colorado River Basin (USA). Melted snow from this basin is the major water source for 44 million people in the arid American Southwest. We found that three types of dust particles contributed most to heat absorption on snow surfaces: iron oxide minerals, dark rock fragments, and soot. The minerals and rock fragments originated in dust storms in deserts adjacent to the mountains, whereas the soot, which was associated with metals, was produced during fossil‐fuel combustion likely from many widespread industrial activities. Similar analyses of dust‐on‐snow from other areas would help evaluate the influences of varied dust sources, wind‐storm patterns, and anthropogenic inputs on snow melt in and beyond the Colorado River Basin. Key Points: We characterized light‐absorbing particles (LAPs) in atmospheric dust deposited on snow cover, San Juan Mountains, Colorado, 2011–2016 The primary LAPs were ferric oxide minerals and dark rock particles mostly from dust storms, and black‐carbon from industrial sources The results are relevant to snow‐radiation modeling and water‐resource management in the Colorado River Basin